Preparação e caracterização de biossensores baseado na eletrocodeposição de grafeno/polipirrol/acetilcolinesterase para determinação de pesticidas em amostras de frutas e vegetais - Camargo, João Pedro Corrêa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
A new biosensor was developed by a simple electrocodeposition of reduced graphene oxide (rGO), polypyrrole (PPy) and the enzyme acetylcholinesterase (AChE) on surface of platinum (Pt) electrode. In potential range of -0.2 to +0.5 V vs. Ag/AgCl/KCl (3.0 mol L-1), using differential pulse voltammetry (DPV), it was observed a process in + 0.1 V and this corresponds to the dimerization of electrochemical oxidation products of thiocholine, resulting in ditio-bis-choline. The biosensor developed was evaluated using DPV in the analysis of carbaryl, which inhibits the AChE enzyme action. The best results achieved were with the followings optimized conditions: 75 mV pulse amplitude, step potential of 4 mV, and a phosphate buffer solution (PBS) 0.2 mol L-1 and pH 6.0. Using these parameters was observed a linear response to carbaryl in a range of 0.1 to 0.5 µmol L-1, with a detection limit of 11.6 nmol L-1 (2.3 µg/kg), which is an appropriate limit for determination of carbaryl in the cultures which these pesticide is applied, considering the maximum reside limit allowed by Brazilian legislation. The biosensor proposed, Pt/rGO/PPy/AChE, was applied successfully in the determination of carbaryl in samples of cabbage and tomato.

Um novo biossensor foi desenvolvido baseado na simples eletrocodeposição do óxido de grafeno reduzido (rGO), polipirrol (PPy) e da enzima acetilcolinesterase (AChE) na superfície do eletrodo de platina (Pt). No intervalo de potencial -0,2 a +0,5 V vs. Ag/AgCl/KCl (3,0 mol L-1), utilizando voltametria de pulso diferencial (DPV), observou-se um processo em +0,1 V e este corresponde a dimerização dos produtos de oxidação eletroquímica da tiolcolina, formando ditio-bis-colina. O biossensor desenvolvido foi avaliado utilizando DPV na análise do pesticida carbaril, o qual inibe a ação da enzima AChE. Os melhores resultados obtidos foram com as seguintes condições otimizadas: 75 mV amplitude de pulso, incremento de potencial de 4 mV, e uma solução tampão fosfato (PBS) 0,2 mol L-1 pH 6,0. Usando tais parâmetros observou-se uma resposta linear para o carbaril no intervalo de 0,1 a 0,5 mol L-1, com um limite de detecção de 11,6 nmolL-1 (2,3 µg/kg), que é um limite adequado para determinar carbaril nas culturas em que este pesticida é aplicado considerando o limite máximo de resíduo permitido pelas legislações brasileiras. O biossensor proposto, Pt/rGO/PPy/AChE, foi aplicado com sucesso na determinação de carbaril em amostras de tomate e repolho.
Preparation and characterization of biosensors based on the electrocodeposition of graphene/polypyrrole/acetylcholinesterase for the determination of pesticides in fruit and vegetable samples
Keywords: Biossensores; Nanotecnologia; Carbaril; Imobilização; Acetilcolinesterase; Biosensor; Nanotechnology; Carbaryl; Immobilization; Acetylcholinesterase